Edukasi Dan Skrining Asam Urat Sebagai Deteksi Dini Batu Saluran Kemih Pada Usia Produktif - Nicholas Albert Tambunan; Alexander Halim Santoso; Farell Christian Gunaidi; Anak Agung Ngurah Putrayoga Amertha; Rifandra Rifqi Adi Hendrianto (Gotong Royong, 2025)
Hyperuricemia, characterized by elevated serum uric acid levels, is a health issue that has the potential to cause serious complications such as urinary tract stones and kidney disorders, particularly in the productive-age population. This community service program was implemented using the PDCA method in Danau Sunter, North Jakarta, involving 49 adult participants. The activities included uric acid level screening through blood tests, result analysis, and educational sessions on the prevention and management of hyperuricemia. The screening results showed that all participants had uric acid levels within the normal range. The educational intervention aimed to raise awareness about the importance of a healthy lifestyle in preventing long-term complications. This program demonstrates that screening and education can be effective strategies for the early detection and prevention of urinary tract stones and for maintaining kidney health among productive-age individuals. Keywords: Hyperuricemia, Uric Acid, Urinary Tract Stones, Education, Productive Age